Challenges for university teaching: the relationship between psychology and education as interlocutor of the subjects (trans) personal and collective training - Magalhães, Solange M. O. (Revista Hipótese, 2015)
The Educational Psychology is one of the academic disciplines of teachers, it shows an area of research with implications for learning and university education. With regard to education, the teaching of psychology enables understanding of complex educational task in the classroom and in the socio-cultural context. With regard to education, the teaching of psychology enables understanding of complex educational and socio-cultural task. However, teachers need to understand the psychological knowledge as useful to improve the content of their teaching practice. In this sense, it is placed a challenge for university teaching: promoting understanding of the existence of interconnections between the subject and the object of knowledge, through understanding the emotional nature can be understood as an object of knowledge, giving them thus an new cognitively in their lives, such as biology and mathematics can be seen as objects of knowledge. This reflection is an innovative approach in the field of training, it marks the search for enhancement of educational psychology content and is intended to (trans) formation of personal subjects and collectively.
Keywords: Psychology; Education; University teaching